PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEPUASAN KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA WARUNG MINA PEGUYANGAN - Purpa, Tri Satria Putri; Sudharma, I Nyoman (E-Jurnal Manajemen; Vol 4 No 3 (2015), 2015)
The purpose of this study was to determine the effect of transformational leadership, job satisfaction, and organizational commitment on organizational citizenship behavior in Warung Mina Peguyangan. This study uses a quantitative research using surveys and questionnaires to 66 employees Warung Mina Peguyangan. Data analysis techniques used in this research is multiple linear regression. Obtained findings that simultaneous variables of transformational leadership, job satisfaction, and organizational commitment significantly influence variables on employee organizational citizenship behavior Warung Mina Peguyangan. Second, partial, variable transformational leadership, job satisfaction, and organizational commitment and significant positive effect on organizational citizenship behavior in employees Warung Mina Peguyangan. Finally, the variables of organizational commitment (X3) is a variable that has the most impact on employee organizational citizenship behavior Warung Mina Peguyangan.
Keywords: Transformational Leadership, Job Satisfaction, Organizational Commitment, Organizational Citizenship Behavior